Frequency of Metabolic Syndrome and Its Components in Family Medicine Department of Military Hospital - Nudrat, Ayesha; Sadaf Nawaz; Namrah Fatima Mujeeb; Hafiz Muhammad Usama; Hadia Tahir; Waleed Ur Rehman (Pakistan Armed Forces Medical Journal, 2026)
Objectives: To determine frequency of metabolic syndrome and its components in patients presenting at the family medicine department of Pak Emirates Military Hospital.Study Design: Cross-sectional study.Place and Duration of Study: Department of Family Medicine, Pak Emirates Military Hospital (PEMH), Rawalpindi Pakistan, from Jun to Nov 2023.Methodology: A total of 305 patients who presented at the current family medicine department for their general health checkup were included in the study, based on NCEP: ATP III criteria. All patients were screened for metabolic syndrome (MetS) as well as its individual components. Data was analyzed using SPSS 22:00.Results: Mean age was 51.90±7.86 years. 43(60.56%) were males, and 28(39.44%) were females. Frequency of Metabolic Syndrome (MetS) was 23(32.39%). Frequency of raised FBG was 29(40.85%), of increased WC was 31(43.66%), of raised BP was 31(43.66%), of low HDL-cholesterol was 25(35.21%), and of raised serum TG was 12(16.90%). In addition, in patients who did not meet the criteria of MetS (n=48), frequency of raised FBG was 6(12.50%) of increased WC was 8(16.66%), of raised BP was 20(41.66%), of low HDL-cholesterol was 2(4.16%) and of raised serum TG was 6(12.50%).Conclusion: Metabolic syndrome (MetS) was found in 32.39% of the population, which is alarmingly high.